2016
DOI: 10.2147/ndt.s64672
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of paliperidone in the treatment of schizophrenia in Chinese patients: a systematic literature review

Abstract: BackgroundPaliperidone (9-hydroxyrisperidone), the major active metabolite of risperidone, has been introduced as a novel atypical antipsychotic agent in many countries. It is available both as an oral extended-release (ER) formulation and as a long-acting injection (paliperidone palmitate, PP), which have been approved for treating schizophrenia in the People’s Republic of China since 2009 and 2012, respectively. This systematic review summarizes the efficacy, effectiveness, and safety of paliperidone in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“… 26 The efficacy and safety of paliperidone ER for the treatment of schizophrenia, including the use of a flexible dose regimen, have also been confirmed in the Chinese population. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“… 26 The efficacy and safety of paliperidone ER for the treatment of schizophrenia, including the use of a flexible dose regimen, have also been confirmed in the Chinese population. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…A recent network meta-analysis, comparing the efficacy, acceptability and tolerability of 8 atypical antipsychotics in Chinese patients with acute schizophrenia, demonstrated paliperidone ER to be in a position of superior efficacy with lower discontinuation risk 20. Another systematic review summarizing the clinical evidence of the efficacy, effectiveness and safety of paliperidone in the Chinese population reported that paliperidone ER demonstrated superior improvement in the PSP scores and at least comparable efficacy with active comparators assessed 15. The documented efficacy and safety profile of paliperidone ER and its positive effect on functional status may contribute to the improvement in patient satisfaction with the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Paliperidone extended-release (paliperidone ER), marketed as Invega ® (Janssen Pharmaceutica, Beerse, Belgium), is a once-daily atypical antipsychotic tablet formulation approved for the treatment of schizophrenia in the People’s Republic of China in 2009 15. Paliperidone is the major active metabolite of risperidone, and it acts as an antagonist of dopamine-2 (D2) receptors and 5-hydroxytryptamine 2A (5-HT2A) receptors, with a higher affinity for 5-HT2A receptors 15,16.…”
Section: Introductionmentioning
confidence: 99%
“…Although paliperidone is the active metabolite of risperidone 9-hydroxyrisperidone, previous clinical studies have shown that the pharmacological characteristics of paliperidone are not exactly the same as risperidone 8. Paliperidone has a slightly higher affinity for dopamine D1, D2, D3 and D5 receptors and a higher affinity for norepinephrine α2 and 5-HT7 receptors when compared with risperidone 9. The alpha 2 methadrenergic receptor in the prefrontal cortex plays an important role in the mediation of cognitive function,10 and 5-HT7 receptor plays an important role in emotion, learning and memory and endocrine regulation 11.…”
Section: Discussionmentioning
confidence: 98%